A simulation study of warehouse loading and unloading systems using ARENA - Liong, Choong-Yeun; Loo, Careen S.E. (Penerbit ukm, 2009)
In a warehouse, all the processes in the loading and unloading systems are run simultaneously. In this paper, animated ARENA simulation models for the loading and unloading systems in a warehouse are presented and discussed. The aim of the study is to find a strategy that will optimise the residence time of any lorry in the warehouse. The warehouses of interest are those that deal with already packed as well products that need sealing. The processes in the unloading system are checking, unloading, arranging and sealing, and storage of products; whereas for the loading system, the processes are processing the delivery order, picking and sealing, loading, and checking the load on the lorry. A simulation model of the existing system was developed and run to further understand the state of the operations. Utilisation of workers and waiting times at the various processes were discussed and analysed to identify the bottleneck in the system. It was identified that the interarrival time of customers’ lorries; waiting time at the order picking, sealing and loading process; and the number of forklift are the contributing factors towards the performance of the loading system. The unloading system, which uses the company own lorry, has no bottleneck because the lorry is well scheduled. Four improvement models were developed and compared. It was found that, when other factors are relatively the same, by adding a forklift and a driver, the chosen model has not only overcome the overtime problem but also reduces the waiting time of the customers by almost two hours, i.e. by more than 65%